Theories and Documents of Contemporary Art: A Sourcebook of Artists' Writings - Stiles, Kristine; Selz, Peter 1919-2019 (Berkeley Los Angeles London University of California Press, 1996)
Ambitious and interdisciplinary, this long-awaited collaboration is a landmark presentation of the writings of contemporary artists. These influential essays, interviews, and critical and theoretical comments provide bold and fertile insights into the construction of visual knowledge. Featuring a wide range of leading and emerging artists since 1945, the collection--while comprehensive and authoritative--offers the reader some eclectic surprises as well.Included here are texts that have become pivotal documents in contemporary art, along with writings that cover unfamiliar ground. Some are newly translated, others have never before been published. Together they address visual literacy, cultural studies, and the theoretical debates regarding modernism and postmodernism. The full panoply of visual media is represented, from painting and sculpture to environments, installations, performance, conceptual art, video, photography, and virtual reality. Thematic concerns range from figuration and process to popular culture, art and technology, and politics and the media. Contemporary issues of gender, race, class, and sexuality are also addressed.Kristine Stiles's general introduction is a succinct overview of artists' theories in the evolution of contemporary discourse around art. Introductions to each chapter provide synopses of the cultural contexts in which the texts originated and brief biographies of individual artists. The text is augmented by outstanding photographs, many of artists in their studios, and vivid, contemporary art images.Reflecting the editors' shared belief that artists' own theories provide unparalleled access to visual knowledge, this book, like its distinguished predecessors, Hershel Chipp's Theories of Modern Art (with Peter Selz and Joshua Taylor) and Joshua Taylor's Nineteenth-Century Theories of Art, will be an invaluable resource for anyone interested in contemporary art."In New York in 1915 I bought at a hardware store a snow shovel on which I wrote 'in advance of the broken arm.' It was around that time that the word 'readymade' came to mind to designate this form of manifestation."--Marcel Duchamp (1961)"Women have always collected things and saved and recycled them because leftovers yielded nourishment in new forms. The decorative functional objects women made often spoke in a secret language, bore a covert imagery. When we read these images in needlework, in paintings, in quilts, rugs and scrapbooks, we sometimes find a cry for help, sometimes an allusion to a secret political alignment, sometimes a moving symbol about the relationships between men and women."--Miriam Schapiro and Melissa Meyer (1978)"I want to create a fusion of art and life, Asia and America, Duchampiana modernism and Levi-Straussian savagism, cool form and hot video, dealing with all of those complex problems, spanning the tribal memory of the Nomadic Asians who crossed over the Bering Strait over 10,000 years ago."--Shigeko Kubota (1976)"Black for me is a lot more peaceful and gentle than white. White marble may be very beautiful, but you can't read anything on it. I wanted something that would be soft on the eyes, and turn into a mirror if you polished it. The point is to see yourself reflected in the names. Also the mirror image doubles and triples the space."--Maya Lin (1983)"Artists often depend on the manipulation of symbols to present ideas and associations not always apparent in such symbols. If all such ideas and associations were evident there would be little need for artists to give expression to them. In short, there would be no need to make art."--Andres Serrano (1989)
Keywords: 20th Century (1901-2000); art philosophy & esthetics; Philosophy; Fine art